Biochemistry of Vibrio cholerae Virulence I. Purification and Biochemical Properties of PF/Cholera Enterotoxin - Richardson, Stephen H. (1970)
A simple method for concentrating, isolating, and purifying PF/cholera enterotoxin from culture supernatant fluids is presented. Precipitation with dextran sulfate and ammonium sulfate, followed by gel filtration and ion-exchange chromatography, yielded PF/enterotoxin of high biological potency. Although not completely free from traces of vibriocidal antibody-stimulating activity, the resultant purified toxic immunogen appeared homogeneous as judged by immunoelectrophoresis, immunodiffusion, and disc electrophoresis. Advantages and disadvantages of this purification method are discussed in comparison with those of previously published techniques.